2021
DOI: 10.1002/ajb2.1719
|View full text |Cite
|
Sign up to set email alerts
|

Molecular framework underlying floral bilateral symmetry and nectar spur development in Tropaeolum, an atypical member of the Brassicales

Abstract: Premise: Floral spurs are key innovations associated with elaborate pollination mechanisms that have evolved independently several times across angiosperms. Spur formation can shift the floral symmetry from radial to bilateral, as it is the case in Tropaeolum, the only member of the Brassicales with floral nectar spurs. The genetic mechanisms underlying both spur and bilateral symmetry in the family have not yet been investigated. Methods: We studied flower development and morphoanatomy of Tropaeolum longifoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 45 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…In contrast, no KNOX gene expression was detected in the transcriptome of early spurs and in in situ hybridization in a broader development stage [ 27 ]. Studies on Tropaeolum showed that both TCP and KNOX genes may be involved in spur development and play a crucial role in extreme adaxial-abaxial asymmetry [ 28 ]. Furthermore, coregulated gene groups that mediate hormone synthesis or response also participate in spur development.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, no KNOX gene expression was detected in the transcriptome of early spurs and in in situ hybridization in a broader development stage [ 27 ]. Studies on Tropaeolum showed that both TCP and KNOX genes may be involved in spur development and play a crucial role in extreme adaxial-abaxial asymmetry [ 28 ]. Furthermore, coregulated gene groups that mediate hormone synthesis or response also participate in spur development.…”
Section: Introductionmentioning
confidence: 99%